Notons S(n)=Somme de k=1 à k=n des k/(k+1)!
Pour n=1 on a S(1)=1/(1+1)!=1/2!
2!=1x2=2 (Rappel : factorielle k = k! =1x2x3x4x.....x(k-1)xk
Donc S(1)=1/2
1-1/(1+1)!=1-1/2=1/2
donc au rang n=1 on a bien S(1)=1-1/(1+1)!
Supposons qu'au rang n, on ait S(n)=1-1/(n+1)!
S(n+1)=S(n)+(n+1)/(n+2)!=1-1/(n+1)!+(n+1)/(n+2)!
1-1/(n+1)!+(n+1)/(n+2)!=1-(n+2)/((n+1)!*(n+2))+(n+1)/(n+2)!
Or (n+1)!*(n+2)=(n+2)! donc :
1-1/(n+1)!+(n+1)/(n+2)!=1-((n+2)-(n+1))/(n+2)!=1-1/(n+2)!
Donc S(n+1)=1-1/(n+2)!
Donc quelque soit n : S(n)=1-1/(n+1)!